Plurilateralism within the WTO as a Catalyst for New Trade Linkages: An Analysis of the JSI on E-Commerce - Comont, Antoine (Revue Interventions économiques / Papers in Political Economy, 2026)
This article analyzes the potential of the WTO's Joint Initiative on Electronic Commerce (JSI) as a catalyst for fostering e-commerce while meeting sustainable development issues. It explores the challenges of the transition from multilateralism to plurilateralism and traces the genesis of the Joint Initiative on Electronic Commerce. After providing an overview of the provisions of the draft agreement, the article aims to analyze the extent to which development issues have been taken into account by exploring the tensions arising from the negotiations. Inevitably, it identifies the major shortcomings that remain, particularly in terms of environmental sustainability and the inclusion of developing countries. Finally, looking to the future, the article examines the options for integrating this agreement into the WTO legal order.